The properties of central-orbital types of EPSCJ theories - Yeshkeyev, A.R. (Publ.KarSU, 2017)
This article, in its content, refers to the study of the theoretical-model properties of the Jonsson theories. A new approach to this study is proposed. As a new notion, the idea of a central-orbital type is used. When studying Jonsson theories are taken into account the following facts:Syntactic, concerning the Jonsson theories and the Jonsson subsets of the semantic model of the Jonsson theory under consideration.In addition, a special role in the syntactic sense is played by the enrichment of the signature associated with the given Jonsson sets. The semantic aspect of the issues under consideration is primarily concerned with the notion of convexity, strong convexity, and existential primeness.Although these definitions are related to theory, in fact we are dealing with different types of models that are existentially closed.
EPSCJ теорияларды централды-орбиталды тyрлерiнi қасиеттерi
Свойства центрально-орбитальных типов EPSCJ теорий
Keywords: Jonsson theory; Jonsson set; fragment of Jonsson sets; Existentially Prime Strongy Convex Jonsson theories; central-orbital types